2019
DOI: 10.1248/bpb.b19-00260
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Ephedra Herb Extract, Ephedrine Alkaloids–Free Ephedra Herb Extract, Ephedrine, and Pseudoephedrine on Formalin-Induced Pain

Abstract: The analgesic effect of Ephedra Herb (EH) is believed to be derived from the anti-inflammatory action of pseudoephedrine (Pse). We recently reported that ephedrine alkaloids-free EH extract (EFE) attenuates formalin-induced pain to the same level as that achieved by EH extract (EHE), which suggests that the analgesic effect of EH may not be due to ephedrine alkaloids (EAs). To examine the contribution of EAs to the analgesic effect of EH, mice were injected with formalin to induce a biphasic pain reaction (fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…NGF is an inflammatory mediator and NGF-Trk A signalling is involved in inducing pain and itching [ 134 ]. Therefore, we investigated the analgesic effect of herbacetin using the formalin test [ 139 ]. The results suggested herbacetin suppressed the second phase of formalin-induced pain in a dose-dependent manner.…”
Section: Regulatory Science For New Ethical Drugs Derived From Herbal...mentioning
confidence: 99%
“…NGF is an inflammatory mediator and NGF-Trk A signalling is involved in inducing pain and itching [ 134 ]. Therefore, we investigated the analgesic effect of herbacetin using the formalin test [ 139 ]. The results suggested herbacetin suppressed the second phase of formalin-induced pain in a dose-dependent manner.…”
Section: Regulatory Science For New Ethical Drugs Derived From Herbal...mentioning
confidence: 99%
“…Recently, we found that EFE relieves inflammatory pain. 13,14) Therefore, we examined the analgesic effects of each fraction isolated from EFE using the formalin test in vivo. The formalin test is widely used to evaluate analgesic effects.…”
Section: Identification Of Active Fractions From Ehe With Inhibitory mentioning
confidence: 99%
“…7). 13 C-NMR spectra were measured for the Fr. (a) that showed significant c-Met inhibitory activity.…”
Section: Identification Of Active Fractions From Ehe With Inhibitory mentioning
confidence: 99%
See 1 more Smart Citation
“…Ephedra alata was an important source of several pharmaceutical compounds such of cardiac glycosides, reducing sugars, avonoids, phenolic compounds, and alkaloids; and as Signi cant medicinal properties of this genus were reported such as antimicrobial, antioxidant, antidiabetic, hepatoprotective, cardiovascular, and anticancer effects [13][14][15][16]. Previous studies have reported that Ephedra Herb may have applications in cancer therapy and suppressed cancer metastasis by inhibiting cancer cell motility [17,8,9] and prevented hepatocyte growth factor (HGF)-induced cancer cell motility by inhibiting phosphorylation of the c-Met receptor [17].…”
Section: Introductionmentioning
confidence: 99%